2009
DOI: 10.1093/jb/mvp045
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluation of M-LAO, L-Amino Acid Oxidase, from the Venom of Gloydius blomhoffi as an Anticoagulant Protein

Abstract: Many anticoagulant proteins have been found from snake venoms. Recently, (L)-amino acid oxidase (LAO) from the venom of Gloydius blomhoffi, M-LAO, was reported to inhibit coagulation factor IX; however, the mechanism of its anticoagulant activity is still unclear. Here, we re-evaluated the anticoagulant activity of M-LAO. We first purified M-LAO from the venom of G. blomhoffi, and examined the effect of LAO inhibitors and the hydrogen peroxide scavenger, catalase, on the anticoagulant activity of M-LAO. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Furthermore, it was the direct deaminating action of LAAO, not the coincident generation of H 2 O 2 , that was responsible for the coagulation procoagulant profile as demonstrated by the GSH addition experiments. Further, the experiments involving CORM-2 demonstrated functionally, that the procoagulant effects of LAAO were not affected as was the phospholipase A 2 and raw venom activity of Crotalus adamanteus [6,7,8]. The lack of inhibition of the LAAO activity by EDTA and the transformation of procoagulant to anticoagulant activity by PMSF further confirmed that the phenomena observed in this system were LAAO mediated.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, it was the direct deaminating action of LAAO, not the coincident generation of H 2 O 2 , that was responsible for the coagulation procoagulant profile as demonstrated by the GSH addition experiments. Further, the experiments involving CORM-2 demonstrated functionally, that the procoagulant effects of LAAO were not affected as was the phospholipase A 2 and raw venom activity of Crotalus adamanteus [6,7,8]. The lack of inhibition of the LAAO activity by EDTA and the transformation of procoagulant to anticoagulant activity by PMSF further confirmed that the phenomena observed in this system were LAAO mediated.…”
Section: Discussionmentioning
confidence: 69%
“…One preliminary report demonstrated a selective inhibition of coagulation factor IX (FIX) by a purified LAAO obtained from Agkistrodon halys blomhoffii venom [7]. However, in a follow-up investigation by another group investigating the same purified protein, it was determined that the anticoagulant effects of the LAAO were secondary to a contaminant metalloproteinase [8]. Of interest, the original investigation included thrombelastography as part of their analyses [7], and the data was consistent with a contact protein inhibitor mediating anticoagulation when compared to data obtained from FIX deficient plasma [9], a pattern yet to be demonstrated with an isolated metalloproteinase.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of each marker from day 0 to 7 in patients with mamushi bites of grade 2/3 and grade 4 (mean ± SD) is listed in Supplemental Table. It is known that mamushi venom exerts a primary effect on coagulation, 5 and the following consumption of coagulants and the anticoagulant effect of toxins leads to bleeding tendency and muscular and nephrological damages 4,7 . Furthermore, the venom directly promotes vascular permeability and affects vascular endothelial cells 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Snake venom LAAO also activates or inhibits platelet aggregation, depending likely on the experimental procedures [ 38 , 39 ], and can provoke hemorrhage. Apart from their toxicity towards endothelial cells, coagulation defects might result from inhibition of the activity of coagulation factor IX [ 40 ], but this latter effect is still a matter of debate [ 41 ]. Finally, snake venom LAAO can cause hemolysis and edema [ 42 ] and displays anti-bacterial activity, like all LAAOs described so far [ 43 ].…”
Section: Laao Expression and Functionsmentioning
confidence: 99%